Science communication under pressure: perspectives of Dutch researchers and journalists on COVID-19 communication challenges - de Jong, Anouk; Dijkstra, Anne M.; MacLeod, Miles A. J.; de Jong, Menno D. T. (Frontiers in Communication, 2024)
Introduction: Having access to information about science is essential for citizens to relate to global challenges. The COVID-19 pandemic is a clear example of how citizens' dependency on scientific information increased. This study aimed to gain an understanding of the challenges researchers and journalists encountered in communicating about COVID-19 and included an analysis of their roles and responsibilities in science-media interactions. Method: Semi-structured interviews were conducted with experienced journalists (n=10) and prominent academic researchers in fields relevant to in the Netherlands. Results: Results show that the pandemic highlighted several challenges in science-media interactions. The pandemic's complexity, uncertainty, and large societal impact put pressure on researchers and journalists who dealt with the societal need for relevant information and combatting misinformation. In response to the challenges they encountered, researchers and journalists had frequent and ongoing interactions with each other. For researchers, this raised the issue of how to balance their responsibilities to inform and advise as public experts. For journalists, this highlighted the need to avoid reporter-source intimacy and remain independent and critical when reporting about science. Conclusion: These findings raise new issues on the roles and responsibilities of researchers and journalists in urgent, fast-moving contexts such as those experienced during the pandemic and other global challenges. Successful responses to challenges such as dealing with misinformation and preprints require further reflection on the roles and responsibilities of both actors.